Novel Aspects of Gas Chromatography and Chemometrics - Moldoveanu, Serban C.; Dang Hoang, Vu; David, Victor (IntechOpen, 2023)
Novel Aspects of Gas Chromatography and Chemometrics presents selected aspects of gas chromatography and chemometrics in which progress has recently been made. The aim of the book is to present up-to-date information on technologies, methods and applications in this field in a coherent, unified form. The book is addressed to a wide audience of analytical chemists and should be of interest to research chemists working in both industry and academia.